Structural changes in the S(3) state of the oxygen evolving complex in photosystem II - Hatakeyama, Makoto (Chem Phys Lett, 2016)
The S(3) state of the Mn(4) CaO(5) -cluster in photosystem II was investigated by DFT calculations and compared with EXAFS data. Considering previously proposed mechanism; a water molecule is inserted into an open coordination site of Mn upon S(2) to S(3) transition that becomes a substrate water, we examined if the water insertion is essential for the S(3) formation, or if one cannot eliminate other possible routes that do not require a water insertion at the S(3) stage. The novel S(3) state structure consisting of only short 2.7–2.8 Å Mn—Mn distances was discussed.